Gene–gene interactions between DRD3, MRP4 and CYP2B6 polymorphisms and its influence on the pharmacokinetic parameters of efavirenz in HIV infected patients. Issue 5 (October 2016) - ,; Bustos, Carmen; Cordero, Miguel; Fuertes, Aurelio; Iglesias, Alicia; Luna, Guillermo; Valverde, M Paz; Sánchez-Martín, Almudena; Cabrera Figueroa, Salvador; Cruz, Raquel; Porras-Hurtado, Liliana; Calvo-Boyero, Fernando; et al.
Abstract: Genetic factors have a significant impact on the PK variability of EFV, much higher than other non-genetic factors, such as demography. In this work we have performed a comprehensive PG analysis of genes encoding the major metabolizing enzymes and transporters of EFV, establishing a clear relationship between the PK parameters and genetic factors, which explain 50% of the variability in EFV PK parameters. The most relevant associations for metabolizing enzymes were found in CYP2B6 (rs3745274), in agreement with previous studies. The influence of transporters on the kinetics of EFV was also proved with significant correlations between the PK parameters of EFV and MRP4 (rs1751034, rs2274407). Analysis of gene–gene interactions with CYP2B6 was particularly useful to reinforce the role of MRP4 and to reveal unknown associations, such as that of DRD3. However, the role of DRD3 cannot be a direct effect but an indirect one due to physical proximity of NAT and the DRD3 locus in the genome.